VP02 Involving Patients In HTA Beyond 2020: A Thematic Review. (2019) - Livingstone, Heidi; Li, Xia; Leng, Gillian; Thomas, Victoria
Abstract : Introduction: Involving patients and the public in the health technology assessment (HTA) is crucial and a key part of the NICE patient and public involvement (PPI) policy. To advance the development of our PPI policy in HTA and build capacity for 2020 and beyond, we took stock of knowledge on stakeholders' views of involving this cohort in HTA. Methods: We carried out a thematic review of the existing evidence on the involvement of patients and the public in HTA, including: technology appraisals consultation 2017 (110 comments): technology appraisals consultation 2018 (205 comments); and PIP review consultation 2017 with a CHTE focus (162 comments). We used Thomas and Harden's (2008) thematic synthesis to code the data 'line-by-line', to develop 'descriptive themes', and then to generate 'analytical themes'. This was followed by using Patton's (1999) triangulation of qualitative data sources to further challenge and refine the emergent themes. Results: We identified three themes, namely (i) earlier and full engagement, (ii) simpler and easier engagement, and (iii) patient evidence. Respondents emphasised the significance of involving patients earlier and throughout the process of developing every appraisal to enable them to gain a greater sense of participation and ownership. Respondents also expressed a strong view of making it simpler and easier for patients to engage in the process through various methods, e.g., standardising the approaches, and support and training. Finally, respondents expressed their positive attitudes toward using patient evidence in HTA, clarifying how patient evidence is captured and used, and offering a clear feedback mechanism to the impact of patient evidence on decision-making. Conclusions: This review highlighted the significance of earlier and full engagement with people, making it simpler and easier for people to work with us, and being clearer about how we use patient evidence with a clearer feedback mechanism as to the impact of their input on the final decisions.